Raphanus Sativus Seed Extract Nanoparticles as Anti-Diabetic Amylolytic Enzyme Inhibitors - Shanti Bhushan Mishra; Pavan Yadav (Nanochemistry Research)
Raphanus sativus L., which belongs to the Brassicaceae family and is commonly known as Radish, is a vegetable grown and consumed around the world as a part of the human diet. All parts, including the seeds, of this plant are intended for diabetes treatment. However, due to the presence of poor water-soluble phytoconstituents and the low bioavailability of seeds, their nanoparticles were prepared by nanoprecipitation followed by the probe sonication method. They were also characterized by FTIR, FESEM, and zeta sizer. In addition, the plant extract was subjected to quantitative estimation of total flavonoid and phenolic compounds. The particle size and polydispersity index of prepared nanoparticles were found to be 203.76±2.24 nm and 0.89, respectively. The Zeta potential of the prepared nanoparticles was -6.29 mV. The in vitro antidiabetic effect of the prepared plant extract and its nanoparticles were estimated using the alpha-amylase and alpha-glucosidase inhibition methods and compared with the standard drug Acarbose, which shows significant inhibition of both amylolytic enzymes in a dose-dependent manner.